Mouse models of atherosclerosis in translational research. (November 2022) - Ilyas, Iqra; Little, Peter J.; Liu, Zhiping; Xu, Yanyong; Kamato, Danielle; Berk, Bradford C.; Weng, Jianping; Xu, Suowen
Abstract : Atherosclerotic cardiovascular disease (CVD), the major cause of premature human mortality, is a chronic and progressive metabolic and inflammatory disease in large- and medium-sized arteries. Mouse models are widely used to gain mechanistic insights into the pathogenesis of atherosclerosis and have facilitated the discovery of anti-atherosclerotic drugs. Despite promising preclinical studies, many drug candidates have not translated to clinical use because of the complexity of disease patho-mechanisms including lipid metabolic traits and inflammatory, genetic, and hemodynamic factors. We review the current preclinical utility and translation potential of traditional [apolipoprotein E (APOE)- and low-density lipoprotein (LDL) receptor (LDLR)-deficient mice] and emerging mouse models that include partial carotid ligation and AAV8- Pcsk9 -D377Y injection in atherosclerosis research and drug discovery. This article represents an important resource in atherosclerosis research. Highlights: A similar lipid profile and disease pathology are important considerations for selecting mouse model of atherosclerosis for translational research. Apoe −/− mice, Ldlr −/− mice, and APOE 3-Leiden. CETP mice are important preclinical models that have been used to validate FDA-approved lipid-lowering drugs. AAV8- Pcsk9 -D377Y injection can induce atherosclerotic plaque formation in C57BL/6J mice without crossbreeding with atherosusceptible mouse strains. Partial carotid ligation surgery in Apoe −/− mice or Ldlr −/− mice creates flow disturbance and emerges as a new model to examine the role of mechanosensitive factors in atherogenesis.